Efficient initiation of radical‐mediated thiol‐ene chemistry with photoactive silica particles. Issue 5 (24th November 2016) - Sahin, Melahat; Schlögl, Sandra; Kaiser, Simon; Kern, Wolfgang; Wang, Jieping; Grützmacher, Hansjörg
ABSTRACT: This work aims at the design of photoactive inorganic filler by covalently attaching tri(methoxy)silyl‐functionalized bis(acyl)phosphane oxides (TEMSI 2 ‐BAPO) onto silica particles. The immobilization of the photoactive groups is evidenced by spectroscopic measurements and thermal gravimetric analysis. The modified particles are then incorporated into thiol–ene resins to study the efficiency of the Norrish type I photofragmentation reaction of the covalently bound TEMSI 2 ‐BAPO derivatives. The photopolymerization kinetics of the thiol–ene system is monitored by FT‐IR spectroscopy and photo‐DSC upon prolonged exposure with UV‐light and compared with the results achieved with IRGACURE 819 (free BAPO). Rapid curing and high conversion yields are obtained evidencing the high efficiency of the photoactive particles. In addition, negative‐toned patterns are inscribed in thin thiol–ene films by photolithographic processes and characterized by microscopic techniques demonstrating the versatile applicability of the photoactive particles. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 894–902 Abstract : Photoactive particles are prepared by immobilizing bis(acyl)phosphane oxide (BAPO) derivatives onto silica surfaces. The photoreactivity of the modified particles is comparable with IRGACURE 819 and enables an efficient initiation of radical‐mediated thiol–ene photopolymerization. Rapid curing and high conversion yields are achieved allowing the fabrication of thin patterned films with 25 µm resolution. The photoactive particles provide a convenient strategy to reduce the amount of extractable residues in thiol–ene compounds.